2020
DOI: 10.1017/s1047951119002646
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with congenital heart defects: a patient and parental perspective of genetic information and genetic risk

Abstract: AbstractCongenital heart defects (CHDs) occur in 8 of 1000 live-born children, making them common birth defects in the adolescent population. CHDs may have single gene, chromosomal, or multifactorial causes. Despite evidence that patients with CHD want information on heritability and genetics, no studies have investigated the interest or knowledge base in the adolescent population. This information is necessary as patients in adolescence take greater ownership of their health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Our results demonstrate that only 37.8% of patients correctly identify their diagnosis, and shockingly, seven patients (5.5%) were unaware that they had a congenital colorectal disorder at all. Sadly, this is in accordance with previous studies that investigated patients' understanding of their congenital colorectal and cardiac anomalies [4,[7][8][9]. Further examination of the group with ARMs found that females were three times more likely to be correct about their condition than their male counterparts.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results demonstrate that only 37.8% of patients correctly identify their diagnosis, and shockingly, seven patients (5.5%) were unaware that they had a congenital colorectal disorder at all. Sadly, this is in accordance with previous studies that investigated patients' understanding of their congenital colorectal and cardiac anomalies [4,[7][8][9]. Further examination of the group with ARMs found that females were three times more likely to be correct about their condition than their male counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…Focus groups of adult patients in Sweden and Norway reported a strong desire to have better information about their condition, bowel function, fertility, and genetic heritability. This sentiment aligns with other studies of people living with chronic health conditions such as congenital heart defects (CHD) [5,7]. Previous studies have explored the knowledge of people born with CHD and have shown that 32-49% were unaware of the diagnosis, or incorrectly it, and that only 50-61% could describe their anomaly, or the related anatomy, in lay terms.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Many adult patients with CHD desire more information about the inheritance of CHDs, specifically in the case of reproductive decision‐making (van Engelen et al., 2011, 2013). Adolescents with CHDs have also expressed interest in receiving education on potential causes of CHDs and their recurrence risks (Crawford et al., 2020). Genetic counselors are a valuable resource to both patients and physicians, as they can consult on genetic testing strategies and family screening recommendations, and provide recurrence risk and psychosocial counseling to families affected by CHDs (Freeze et al., 2016).…”
Section: Introductionmentioning
confidence: 99%